Integrated Analysis of Hepatic miRNA and mRNA Expression Profiles in the Spontaneous Reversal Process of Liver Fibrosis - Tai, Yang; Zhao, Chong; Lan, Tian; Zhang, Linhao; Xiao, Yang; Tong, Huan; Liu, Rui; Tang, Chengwei; Gao, Jinhang (Frontiers in Genetics, 2021)
Liver fibrosis, results from the imbalance between extracellular matrix (ECM) production and degradation, is a common pathological consequence of various chronic liver diseases. Although many miRNAs have been reported in liver fibrosis progression, miRNA-mRNA interactions in its reversal process remain to be elucidated. In the current study, we performed an integrated analysis of miRNA and mRNA expression profiles in the mouse model with the spontaneous reversal potency of liver fibrosis. A total of 102 miRNA and 2,845 mRNAs showed significant differential expression in reversal mice compared to fibrotic mice. Moreover, 3,769 putative negatively correlated miRNA-mRNA pairs were revealed to be potentially implicated in the biological function regulation of small molecule metabolism and ECM organization. By integrating miRNA-mRNA regulatory networks, mmu-miR-1843a-5p, mmu-miR-193a-5p, mmu-miR-194-2-3p and mmu-miR-30c-2-3p were identified as lysyl oxidases-specific miRNAs that were corelated with the fibrosis reverse. Our results provided potential candidate targets for the treatment of liver fibrosis.